Community-based metabolic syndrome screening and herbal beverage training: An intervention in Parepare, Indonesia - Jafar, Nurhaedar; Khuzaimah, Anna; Asfar, Muhammad; Kurniati, Yessy (Sociality: Journal of Public Health Service, 2025)
The prevalence of metabolic syndrome in Indonesia continues to increase, while community-based preventive interventions that integrate early screening and nonpharmacological approaches remain limited. This community engagement program aimed to enhance the capacity of Aisyiyah cadres in Parepare City through training on metabolic syndrome screening and the preparation of herbal beverages as a preventive strategy. A participatory training method was applied, including preparation, socialization, lectures, demonstrations, hands-on practice, mentoring, and evaluation using pre-test and post-test designs. The training focused on improving cadres’ knowledge, attitudes, and skills related to metabolic syndrome risk factors, basic screening procedures, and the utilization of local herbal ingredients. The results showed a marked improvement in participants’ competencies. Before the intervention, most cadres had low levels of knowledge (44%) and moderate attitudes (36%). After the training, the majority demonstrated good knowledge (80%) and positive attitudes (64%). Follow-up evaluation indicated that cadres actively disseminated the information to the community and began promoting healthier lifestyles supported by herbal-based practices. These findings show that community-based training strengthens the role of women health cadres in preventing metabolic syndrome. Integrating herbal beverage preparation adds value by supporting sustainable health promotion and economic empowerment, especially in rural communities.